The Critics of the Critical: A Defence of aPoststructural Reason in International Relations Theory - Nicholls, Esteban (2012)
This paper presents a defense of postructuralism in International Relations (IR) theory. I particular, I focus on three specific assertions made against this approach: the empty critique and the anti-realist (reality-denying) claim and the relativism argument. More specifically, I argue that these common criticisms focus not on what the approach actually says, but on what it refuses to say, and in doing so often engage in a fruitless reiteration of their own theoretical postulates. My analysis places special attention on poststructralism’s circumvention of foundational positions in IR theorizing and the way in which the critiques addressed here fail to capture the reasons for and results of this argumentative choice. In this sense, I also maintain that much of what is useful in poststructural analyses rests not only in what they say, but also in the theoretical paths they evade.